Intercellular Adhesion Molecule-1 (ICAM-1) Polymorphisms and Cancer Risk: A Meta-Analysis - Daye Cheng; Bin Liang (Tehran University of Medical Sciences, 2015)
Background: Intercellular adhesion molecule-1 (ICAM-1) Lys469Glu (K469E) polymorphism and Gly 241Arg (G241R) polymorphism might play important roles in cancer development and progression. However, the results of previous studies are inconsistent. The aim of this study was to evaluate the association between ICAM-1 K469E and G241R polymorphisms and the risk of cancer by meta-analysis. Methods: A comprehensive literature search (last search updated in November 2013) was conducted to identify casecontrol studies that investigated the association between ICAM-1 K469E and G241R polymorphisms and cancer risk. Results: A total of 18 case-control studies for ICAM-1 polymorphisms were included in the meta-analysis, including 4,844 cancer cases and 5,618 healthy controls. For K469E polymorphism, no significant association was found between K469E polymorphism and cancer risk. However, subgroup analysis by ethnicity revealed one genetic comparison (GG vs. AA) presented the relationship with cancer risk in Asian subgroup, and two genetic models (GG+GA vs. AA and GA vs. AA) in European subgroup, respectively. For G241R polymorphism, G241R polymorphism was significantly association with cancer risk in overall analysis. The subgroup analysis by ethnicity showed that G241R polymorphism was significantly associated with cancer risk in European subgroup. Conclusion: ICAM-1 G241R polymorphism might be associated with cancer risk, especially in European populations, but the results doesn't support ICAM-1 K469E polymorphism as a risk factor for cancer